Investor reaction to SPACs' voluntary disclosures - CASTELLANI, Vincent (Institutional Knowledge at Singapore Management University, 2024)
SPACs are formed to combine with and provide a private firm public trading status and a capital infusion. Firms that enter the public market through a SPAC combination are believed to possess greater voluntary disclosure discretion than traditional IPOs as they obtain their public trading status through a merger. Consistent with regulators’ concerns, recent research finds that SPACs use this discretion opportunistically by issuing optimistic guidance. This study examines how investors respond to these disclosures. We find that optimistic projections increase retail purchasing, which is higher than that of institutional purchasing. Additionally, we find that investors partially see through the optimism and exit at the redemption date. Furthermore, we find that institutional investors increasingly divest their holdings for combinations with optimistic projections. Investors as a whole, however, fail to see through the optimism, as combinations with optimistic projections considerably underperform in the two years following the combination.